Henri Bergson and the Mind Body Problem: Overcoming Cartesian Dualism - Gare, Arran (Cosmos and History: The Journal of Natural and Social Philosophy, 2020)
There are few philosophers who have been so influential in their own lifetimes and had so much influence, only to be subsequently ignored, as Henri Bergson (1859-1941). When in April 1922, Bergson debated Einstein on the nature of time, it was Bergson who was far better known and respected. Now Einstein's achievements are known to everyone, but very few people outside philosophy departments have even heard of Bergson. Following Friedrich Schelling and those he influenced, Bergson targeted the Cartesian dualism that permeates the culture of modernity. In doing so, he challenged deep assumptions rooted in and cemented in place by Descartes' philosophy. It this article I will argue that Bergson made considerable progress in this attack on Cartesian dualism, and diverse philosophers subsequently built on his ideas. However, failure to appreciate the source of these ideas has weakened their impact, being scattered among different disciplines by diverse philosophers and scientists who drew upon Bergson's work while forgetting details of his philosophy. This article is an effort to rectify this situation. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->